Dampak Media Digital dalam Meningkatkan Kemampuan Bahasa Indonesia di SDN 10 Tiumang Kabupaten Dharmasraya - Aziizah Khoirunnisaa; Vigo Aldani; Nur Azmi Alwi; Salmaini Safitri Syam (Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This research was made to find out how much digital media affects the level of Indonesian language skills in elementary schools, especially at SDN 10 Tiumang, Dharmasraya Regency. Therefore, this study aims to see how the use of digital media can help students in elementary schools, especially at SDN 10 Tiumang, Dharmasraya Regency, become more proficient in Indonesian. The research data was collected using qualitative methods, which included interviews and observations. The results of the research conducted show that the use of digital media in learning Indonesian can improve such as learner interest and motivation, listening and speaking skills, reading skills, writing skills, and can improve learner collaboration and interaction. In addition, this integration also shows the existence of challenges and solutions regarding the use of digital media in improving Indonesian language skills at the primary school level, such as limited infrastructure, gaps and proficiency in operating digital media, as well as curriculum changes and increasing demands for education are also a challenge for the application of the use of digital media in improving the Indonesian language skills of students at the primary school level, especially at SDN 10 Tiumang, Dharmasraya Regency. Given the challenges that exist in improving elementary school students' mastery of Indonesian, this research also suggests some innovative solutions, one of which is the application of creative reading methods in elementary schools.